1992
DOI: 10.1159/000227023
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Point Mutation of N-<i>ras</i> and K-<i>ras</i> Oncogenes in Myelodysplastic Syndrome and Acute Myelogenous Leukemia

Abstract: We analyzed activating mutations of N-ras and K-ras by the polymerase chain reaction and oligonucleotide hybridization in hematological disorders. Activating mutations of these codons were detected in 4 of 20 cases of myelodysplastic syndrome (MDS) and 15 of 77 cases of acute myelogenous leukemia (AML). Out of 19 cases of MDS and AML who carried active mutations, 7 cases were found to have two or more distinct mutations in activating codons of N-ras and K-ras. Ras mutation was found preferentially in progressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
28
1
2

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 10 publications
1
28
1
2
Order By: Relevance
“…Some studies have reported that KIT or RAS mutations confer a poor prognosis. 28,35,37,44,45 In this cohort of patients we were unable to demonstrate any significant a prognostic impact of RAS or KIT mutations, although this may be due to the fact that treatment was heterogeneous. The lack of a prognostic impact of KIT or RAS mutations is in marked contrast to the strong negative impact of FLT3/ITD mutations in our study population.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…Some studies have reported that KIT or RAS mutations confer a poor prognosis. 28,35,37,44,45 In this cohort of patients we were unable to demonstrate any significant a prognostic impact of RAS or KIT mutations, although this may be due to the fact that treatment was heterogeneous. The lack of a prognostic impact of KIT or RAS mutations is in marked contrast to the strong negative impact of FLT3/ITD mutations in our study population.…”
Section: Discussioncontrasting
confidence: 59%
“…18,19,36,37 RAS mutations in pediatric AML have been previously reported, albeit, in smaller cohorts of patients (10-99 patients), with frequencies of 6-37%. 35,[38][39][40][41][42] In most studies NRAS mutations were more frequent than KRAS mutations, in agreement with our own study in which 14.7% of patients had a NRAS mutation and only 3.3% a KRAS mutation.…”
Section: Discussionmentioning
confidence: 95%
“…[31][32][33][34][35][36] In this study, as in most previous analyses, NRAS-mutations were among the most frequent mutations in MDS (≥6.5% of all cases), 38,41,42,57 and more frequent than FLT3-LM (≤3%). 23,24 Although the reported incidences of NRAS mutations in MDS range widely (probably due to different proportions of MDS subtypes in the various analyses), this study and all mentioned previous analyses found higher frequencies of NRAS mutations in the advanced stages of MDS than in the initial stages.…”
Section: Discussionmentioning
confidence: 62%
“…23,24 Although the reported incidences of NRAS mutations in MDS range widely (probably due to different proportions of MDS subtypes in the various analyses), this study and all mentioned previous analyses found higher frequencies of NRAS mutations in the advanced stages of MDS than in the initial stages. 41,42,57,58 This demonstrates an association between NRAS mutations and MDS transformation. NRAS mutations were further shown to be associated with karyotype evolution, e.g.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation